Investigation of radiative scattering effect of VIP filler materials using a novel statistical formulation. (October 2015) - Choi, Bongsu; Lee, Jaehyug; Song, Tae-Ho
Highlights: Radiative heat transfer in filler material of vacuum insulation panel is studied. Statistical formulation for one-dimensional pure scattering medium is proposed. Effects of optical thickness, wall emissivity and scattering mode are discussed. Abstract: Radiative heat transfer is investigated for each of isotropic and backward scattering patterns to evaluate the radiative thermal conduction of vacuum insulation panels (VIPs). As a means of analysis, a new statistical formulation is proposed and the results are compared with those of diffusion approximation, Monte Carlo method and discrete ordinate interpolation method (DOIM). The results of the statistical formulation agree well with those of Monte Carlo method and DOIM within 1% error, so that it may be regarded as an exact solution method. The results show that the insulation performance of the VIP can be enhanced by increasing the optical thickness or decreasing the wall emissivity. Also, the backward scattering is about twice effective than the isotropic scattering.